Association of an IRF3 putative functional uORF variant with resistance to Brucella infection: A candidate gene based analysis of InDel polymorphisms in goats - Rossi, Ursula; Hasenauer, Flavia Carolina; Caffaro, María Eugenia; Raschia, Maria Agustina; Maurizio, Estefania; Cortez, Hector Sergio; Neumann, Roberto Daniel; Poli, Mario Andres; Rossetti, Carlos Alberto (Elsevier, 2019)
Brucellosis is an important zoonotic disease caused by infection with Brucella spp. It generates major economic losses in livestock production worldwide. Goats are the principal hosts of B. melitensis, the main infection agent of caprine and human brucellosis. The selection of resistance-related genes is considered one of the best long-term means to improve control to bacterial infection in domestic ruminants. We performed a candidate gene association study to test if six short insertion/deletion polymorphisms (InDels) at bacterial-infection related genes influence the resistance to Brucella infection in female creole goats. InDels (IRF3-540: rs660531540, FKBP5-294: rs448529294, TIRAP-561: rs657494561, PTPRT-588: rs667380588, KALRN-989: rs667660989 and RAB5a-016: rs661537016) were resolved by PCR-capillary electrophoresis in samples from 64 cases and 64 controls for brucellosis. Allelic frequencies were significantly different between cases and controls at IRF3-540 and KALRN-989 (p = 0.001 and 0.005). Indeed, the minor alleles (a and k) at InDels IRF3-540 and KALRN-989 were more frequent among controls than cases, providing evidence that these alleles confer protection against Brucella infection. Moreover, IRF3-540 a-containing genotypes (Aa and aa) were associated with absence of Brucella-specific antibodies in goats (p = 0.003; OR = 3.52; 95% CI = 1.55–7.96), and more specifically, a-allele was associated with resistance to Brucella infection in a dose-dependent manner. Also, we observed that the IRF3-540 deletion (a-allele) extends a conserved upstream ORF by 75 nucleotides to the main ORF, and thus it may decrease gene expression by reducing translation efficiency from the main ORF. These results suggest a potential functional role of IRF3-540 deletion in genetic resistance to Brucella infection in goats.